Cracking risk analysis of face slabs in concrete face rockfill dams during the operation period. (June 2022) - Liu, Yongtao; Zheng, Dongjian; Cao, Enhua; Wu, Xin; Chen, Zhouyan
Abstract: Due to changes in the environmental load and deformation of rockfill bodies, cracks likely form and develop in the face slab of concrete face rockfill dams (CFRDs), affecting the working behaviour of face slabs and the safe operation of dams. At present, the cracking risk in face slabs has not been studied. Based on field test data and the finite element method, this paper developed a new method of analysing the cracking risk of face slabs. Considering that the uncertainty of construction quality leads to the randomization of rockfill material parameters, the probability function and coefficient of variation in the parameters of rockfill materials were determined based on field test data, and then, parameter samples were obtained by Latin hypercube sampling (LHS). The stress of the face slab was calculated by the Duncan-Chang E-B model and Burgers model with the parameter samples. To reduce the calculation workload of the finite element method based on traditional Monte Carlo samples, LHS and the long- and short-term memory (LSTM) algorithm were applied to obtain the response surface function. The LSTM algorithm was used to train the mapping relationship between the material parameters of the samples and the stress of the face slab. Combining the threshold value of the concrete allowable strength with the response surface method, the implicit cracking limit state function of the face slab was approximated, the cracking risk of the face slab was calculated, and the cracking risk curve of the typical area of the concrete face slab with time was given. In this case, mean absolute error (MAE) is 0.006 and the root mean square error (RMSE) is 0.004. The error of this method is very small, meeting the accuracy requirement. The case showed that the results were consistent with the inspection of the face slab and that the method was feasible and effective.